PENGARUH METODE COURSE REVIEW HORAY TERHADAP MOTIVASI BELAJAR SISWA KELAS IV MI BUSTANUL ULUM PADA MATA PELAJARAN MATEMATIKA - Linda Agustian; Sri Enggar Kencana Dewi; Arini Rosa Sinensis (Prodi PGMI STPI Bina Insan Mulia Yogyakarta, 2022)
Learning motivation is very important and very much needed in a learning process. One of the things that affect the high or low motivation to learn is the use of appropriate and appropriate learning methods in the learning process. The purpose of this study was to determine whether or not there was a significant effect on students' motivation by using the course review horay method in the learning process in mathematics. This research was conducted at MI Bustanul Ulum Wonotirto. This research design is quasi-experimental. The population used in this study were all students of class IV MI Bustanul Ulum Wonotirto, totaling 20 students. The sampling technique in this study is non-probability sampling, namely the saturated sample. Students' motivation in this study was measured using a pretest and posttest in the form of a motivational questionnaire which consisted of 12 questions which were declared valid and reliable. Based on the recapitulation of hypothesis testing using a simple linear regression test, the calculated F value is 32,460 with a significance of 0.000, the correlation/influence (R) value is 0.802 and the coefficient of determination (R square) is 0.643 which means that there is an effect of the course review horay method ( independent variable) on students' learning motivation (the dependent variable) of 64.3%.